2015
DOI: 10.1002/adsc.201500773
|View full text |Cite
|
Sign up to set email alerts
|

Amines vs. N‐Oxides as Organocatalysts for Acylation, Sulfonylation and Silylation of Alcohols: 1‐Methylimidazole N‐Oxide as an Efficient Catalyst for Silylation of Tertiary Alcohols

Abstract: A comparison of the relative catalytic efficiencies of Lewisbasic amines vs. N-oxides for the acylation, sulfonylation and silylation of primary, secondary and tertiary alcohols is reported. Whilst the amines are generally superior to the N-oxides for acylation, the N-oxides are superior for sulfonylation and silylation. In particular, 1-methyl-imidazole-N-oxide (NMI-O) is found to be a highly efficient catalyst for sulfonylation and silylation reactions. To the best of our knowledge, NMI-O is the first amine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The corresponding triethylsilyl (TES) ethers were produced in excellent yields wherein N-methylimidazole-N-oxide (NMIO) catalyst activates the silyl chloride as the electrophile in the presence of pentamethylpiperidine (PMP) as a non-nucleophilic stoichiometric base in chloroform as the solvent at 23 C (r.t.). [120] The mentioned authors concluded that this is an efficient silylation system for alcohols as it can be regarded as the first and the most effective non-phosphorus based Lewis-basic catalyst for the silylation of tertiary alcohols with TES-Cl.…”
Section: N-oxides Catalyzed the Silylation Of Hydroxyl Groupsmentioning
confidence: 99%
“…The corresponding triethylsilyl (TES) ethers were produced in excellent yields wherein N-methylimidazole-N-oxide (NMIO) catalyst activates the silyl chloride as the electrophile in the presence of pentamethylpiperidine (PMP) as a non-nucleophilic stoichiometric base in chloroform as the solvent at 23 C (r.t.). [120] The mentioned authors concluded that this is an efficient silylation system for alcohols as it can be regarded as the first and the most effective non-phosphorus based Lewis-basic catalyst for the silylation of tertiary alcohols with TES-Cl.…”
Section: N-oxides Catalyzed the Silylation Of Hydroxyl Groupsmentioning
confidence: 99%
“…The development of practical reagents for the direct conversion of Troc‐protected amines to urea remains a challenge. In particular, organocatalysts are considered an attractive method for synthesizing asymmetrical urea compounds . We are currently interested in identifying catalytic amounts of organic base reagents to treat Troc‐protected amines to directly synthesize target asymmetrical urea compounds in high yield.…”
Section: Screening Of Reaction Conditions For Preparing Urea Structuresmentioning
confidence: 99%
“…In particular, organocatalysts are considered an attractive method for synthesizing asymmetrical urea compounds. 19,20 We are currently interested in identifying catalytic amounts of organic base reagents to treat Trocprotected amines to directly synthesize target asymmetrical urea compounds in high yield. Indeed, a direct synthetic protocol of urea compounds from Troc-protected amines using an organic catalyst has not yet been reported.…”
mentioning
confidence: 99%
“…The base‐catalyzed silylation of alcohols is an often used reaction in synthetic organic chemistry and is of particular importance in protecting group chemistry . While amine‐catalyzed reactions of alcohols with silyl chloride reagents are employed most frequently for this purpose, the alkoxide‐mediated reaction of alcohols with silanes has seen significant progress in recent times . Despite the widespread use of the silyl chloride protection group chemistry, few mechanistic studies document the response of reaction rates to important experimental variables such as solvent, temperature, (catalytically active) additives, substrate structure, and type of reagent .…”
Section: Introductionmentioning
confidence: 99%